Pengaruh Senam Hipertensi Terhadap Tekanan Darah Pada Lanjut Usia Dengan Hipertensi Di Desa Setu Kabupaten Bogor - Hadi Nugroho; Dyah Juliastuti; Liana Pramesti Pramesti (STIKes IMC Bintaro, 2023)
Introduction : The elderly are people who are prone to health problems, the most common of which is the high potential for increased morbidity due to hypertension in the elderly. so that the elderly need sports activities that can improve health, keep the heart, lungs, blood vessels working, and keep the pulse steady. One of the treatments is hypertension gymnastics aimed at increasing blood flow and oxygenation of active muscles and bones, especially the heart muscle. The purpose of this study was to determine the effect of hypertension exercise on blood pressure in hypertensive elderly people in Setu Village. This type of research is quantitative experimental with a one group pretest posttest design approach. The research sample was elderly aged 60-74 years with a non-probability purposive sampling technique. Obtained as many as 12 samples. The results showed that there was a decrease in blood pressure levels by 50%, this means that there was a significant difference between before and after doing hypertension gymnastics so that it was concluded that there was an effect of hypertension gymnastics on hypertensive elderly in Setu Village, Jasinga District, Bogor Regency. His advice is for the elderly to continue to apply hypertension exercise before the level of hypertension increases and the age increases.